Feathering the Nest: The Effects of Feather Supplementation to Blue Tit nests. (June 2016) - Mainwaring, Mark C.; Wolfenden, Andrew; Read, James E.; Robson, Jordan M.A.; Tomlinson, Chris J.; Hartley, Ian R.
Feathers are a widely used nesting material and whilst they may serve to provide thermoregulatory benefits, to repel ectoparasites and/or act as a sexual signal, their exact function remains unclear. Here, we describe a two-part study that examined the function of feathers in Blue Tit ( Cyanistes caeruleus ) nests. In the first part, we supplemented (experimental) Blue Tit nests with individually-marked feathers during nest building and incubation, and examined the fate of those feathers: remain in the original nestbox; removed ( i.e. lost); or moved to neighbouring nestbox. Parents' responses to them and their reproductive success was compared with unsupplemented (control) pairs. Blue Tits at experimental nests generally removed the feathers provided during nest building but generally kept the feathers provided during incubation, providing no support for a thermoregulatory function of feather nest constituents; they retained feathers more often when ambient temperatures were higher later in the spring. As ectoparasite load did not differ between experimental and control nests, feathers appeared to function primarily as sexual signals. We suggest that males during nest building generally removed additional feathers because their introduction mimicked another male attempting to cuckold the resident male. In the second part of the study, we searched for evidence of conspecific nest prospecting and nest material theft by placing individually-marked feathers into the two nestboxes neighbouring each experimental nestbox used in the first part of the study, again both during nest building and incubation. We found no evidence of nest material theft or therefore of conspecific nest prospecting, even when one or both of the neighbouring nestboxes were empty. This suggests that feather availability is not limiting and we conclude that feathers serve primarily as a sexual signal in Blue Tits. However, we were unable to provide any evidence of nest material theft and studies that film both of the parents' responses to the feathers would be useful.